1999
DOI: 10.1034/j.1399-6576.1999.430218.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of pre‐emptive analgesic effect of (R)‐ketamine in laparoscopic cholecystectomy

Abstract: In this study a 1 mg/kg dose of (R)-ketamine given at the end of surgery exerted a short-lasting hypnotic and analgesic effect. The same dose given preoperatively did not show postoperative analgesic effect or pre-emptive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 14 publications
2
43
0
3
Order By: Relevance
“…In the studies of Adam et al, 9 Dahl et al, 11 and Mathisen et al, 12 a single dose of iv ketamine was administered either before surgery, or after surgery. There was no evidence of a pre-emptive effect when ketamine was administered before surgery, and the analgesic effect of ketamine when administered at the end of surgery was short-lasting and failed to produce a significant opioid-sparing effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies of Adam et al, 9 Dahl et al, 11 and Mathisen et al, 12 a single dose of iv ketamine was administered either before surgery, or after surgery. There was no evidence of a pre-emptive effect when ketamine was administered before surgery, and the analgesic effect of ketamine when administered at the end of surgery was short-lasting and failed to produce a significant opioid-sparing effect.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have documented an opioid sparing effect of perioperative iv low-dose ketamine 4-8 and others have not. [9][10][11][12][13][14] These discrepancies may be due to the large interstudy variability in surgical procedures, patient population, dose of ketamine administered, timing of administration, and study design. 15,16 In studies that fail to demonstrate a preventive effect of a low-dose ketamine on postoperative pain, the question of whether a lack of efficacy on central sensitization is linked to insufficient pre-or postoperative blockade remains unresolved.…”
Section: Methodsmentioning
confidence: 99%
“…Após testar várias combinações de morfina e cetamina racêmica em analgesia controlada pelo paciente (ACP) venosa, um estudo verificou que a relação de 1:1 dessa solução promove melhor efeito analgésico e menos efeitos colaterais em pacientes submetidos a cirurgias espinhais ou de quadril 117 . Entretanto, outros estudos não conseguiram demonstrar esse benefício em outros tipos de procedimento cirúrgico [121][122][123] , com uso de R(-) cetamina 124 ou outras doses de cetamina racêmica utilizadas 112,114 . Em crianças, não foi evidenciada potencialização do efeito de opióides com cetamina racêmica por via venosa em apendicectomias 115 , de maneira semelhante a outra pesquisa após amigdalectomia 125 , contrapondo-se ao resultado positivo citado 97 .…”
Section: Estudos Clínicosunclassified
“…After testing different combinations of morphine and racemic ketamine in patient-controlled intravenous analgesia (PCA), a study has observed that 1:1 ratio of this solution promotes the best analgesic effect with less side effects in patients submitted to hip or spinal surgeries 117 . However, other studies were unable to show this benefit in other surgical procedures [121][122][123] with R(-) ketamine 124 or other racemic ketamine doses 112,114 . Potentiation of opioid effects with intravenous racemic ketamine has not been observed in children during appendicectomy 115 , similar to other study after tonsillectomy 125 , in disagreement with the positive result mentioned 97 .…”
Section: Experimental Studiesmentioning
confidence: 99%
“…It has been shown that preincisional infiltration anesthesia with subanesthetic ketamine increases block time, thereby decreasing postoperative analgesic demand (7). The use of ketamine alone as a preventative analgesic remains questionable (8,9).…”
Section: Introductionmentioning
confidence: 99%